2000
DOI: 10.1049/ip-gtd:20000022
|View full text |Cite
|
Sign up to set email alerts
|

TS-fuzzy controller for UPFC in a multimachine power system

Abstract: The unified power flow controller is one of the most versatile flexible AC transmission system devices, which can be used to control the active and reactive power flows in a transmission line by injecting a variable voltage in series and reactive current in shunt. The application of Takagi-Sugeno type fuzzy logic controllers for UPFC voltage source inverter control in a multi-machine power system environment is proposed. This type of fuzzy controller provides a wide range of control gain variation by including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 1 publication
0
34
0
Order By: Relevance
“…The order of the TSK-fuzzy model is given by the order of the polynomial f(x, y). A TSK-type fuzzy controller can provide a wide range of control gain variation and can use both linear and non-linear rules in the consequent expression of the fuzzy rule base [15]. The Mamdani type of fuzzy controller used for the control of SAPF has the drawback of larger number of fuzzy sets and rules.…”
Section: Design Of Tsk-type Fuzzy Logic Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…The order of the TSK-fuzzy model is given by the order of the polynomial f(x, y). A TSK-type fuzzy controller can provide a wide range of control gain variation and can use both linear and non-linear rules in the consequent expression of the fuzzy rule base [15]. The Mamdani type of fuzzy controller used for the control of SAPF has the drawback of larger number of fuzzy sets and rules.…”
Section: Design Of Tsk-type Fuzzy Logic Controllermentioning
confidence: 99%
“…Also it has guaranteed continuity of output surface. Design of a novel variable gain PI-controller using TSK fuzzy model is given in [8,15]. Application of similar controller to SAPF is given in Fig.…”
Section: Design Of Tsk-type Fuzzy Logic Controllermentioning
confidence: 99%
“…One input is designated as a desired input and the other as a disturbance input. The inverse of the plant matrix is given by: = * * * * * * * * * − mm m2 m1 2m 22 21 1m 12 11 1 P P P P P P P P P P(s) (10) The m 2 effective plant transfer function is:…”
Section: Deecentralized Control Designmentioning
confidence: 99%
“…As a result, a fixed parameter controller based on the classical control theory such as PI or lead-lag controller [3,[7][8][9] is not certainly suitable for a UPFC control method. Thus, some authors have suggested fuzzy logic controllers [10] and neural networks method [11] to deal with system parameters changes for enhance system damping performance. However, the param-eters adjustments of these controllers need some trial and error.…”
Section: Introductionmentioning
confidence: 99%
“…This fact has motivated the use of fuzzy logic in the development of fuzzy model based control systems. In this context, The Fuzzy Systems have been widely used due to flexibility of its structure to incorporate linguistic information (knowledge expert) with numerical information (sensors and actuators measurements), as well as its functional efficiency as universal approximator capable of treat adequately uncertainties, parametric variations and nonlinearity of the plant to be controlled (Castro-Sitiriche et al, 2008;Cetin & Demir, 2008;Cheng et al, 2009;Ibrahim, 2003;Mishra et al, 2000;Park et al, 2007;Wen-Xu et al, 2009). Modeling is the task that simplifies a real system or complex reality with the aim of easing its understanding.…”
Section: Introductionmentioning
confidence: 99%